Validity of an ultra-wideband local positioning system to assess specific movements in handball - Fleureau, A.; Lacome, M.; Buchheit, M.; Couturier, A.; Rabita, G. (Biology of Sport, 2020)
The aim of this study was to examine the concurrent validity of the Kinexon local positioning system (LPS) in comparison with the Vicon motion capture system used as the reference. Five recreationally active men performed ten repetitions of linear sprints, medio-lateral side-to-side and handball-specific movements both in the centre and on the side of an indoor field. Validity was assessed for peak speed, peak acceleration and peak deceleration using standardised biases, Pearson coefficient of correlation (r), and standardised typical error of the estimate. With the exception of peak decelerations during specific movements in the centre and peak acceleration and deceleration during linear sprints on the side of the field, the standardised typical error of the estimate (TEE) values were all small to moderate (0.06-0.48), standardised bias ranged between 0.01 and 2.85 and Pearson coefficient values were all > 0.90 for all variables in all conditions. Peak acceleration and deceleration during linear sprints on the side of the field showed the largest TEEs and the greatest differences between the two systems. The ultra-wideband based (UWB) local positioning system had acceptable validity compared with Vicon to assess players` movements in handball with the exception of high accelerations and decelerations during linear sprints on the side of the field.